Genetic techniques for biological research : a case study approach - Michels, Corinne V. Anthony (John Wiley, 2002)
This advanced textbook teaches the theory and practice of molecular genetic analysis to senior undergraduates and graduates studying genetics, molecular biology and cell biology. It uses a case study approach, with the yeast Saccharomyces as the model genetic organism, to explain the theory and practice of molecular genetic analysis. R